Aplicação da norma ABNT NBR IEC 62353:2019 na engenharia clínica: cenário atual no Brasil e importância dos ensaios de desempenho recorrentes e após reparo em equipamentos eletromédicos - Nunes, André Felipe Brescovici (2025)
The ABNT NBR IEC 62353:2019 standard establishes guidelines for conducting recurrent tests and post-repair inspections on electromedical equipment (EMEs), aiming to ensure their performance and electrical safety throughout their service life. This dissertation also aimed to assess the level of knowledge and application of this standard among Clinical Engineering professionals in Brazil, as well as to analyze the practical effectiveness of the recommended tests. The research was conducted in two stages: the first involved a survey with 45 professionals from 17 Brazilian states using a structured questionnaire; the second consisted of applying the tests in a large public hospital, with 393 procedures performed. The results showed that only 22.2% of the institutions perform all standard tests upon equipment reception, 31.1% after repairs, and 48.9% on a recurrent basis. It was observed that knowledge of the standard among professionals is still limited (only 22.2% reported in-depth knowledge), which compromises its practical adoption. Larger healthcare institutions and those with quality certifications showed greater adherence to the standard’s guidelines and better outcomes in the tests. The applied tests identified failures in 9.3% of the equipment, mainly related to protective ground resistance and leakage current in applied parts. The average time to perform the tests was 5.34 minutes, demonstrating their operational feasibility. It is concluded that, although technically applicable and relevant to the safety of EMEs, the standard is still underutilized in national hospital practice. Investments in professional training, infrastructure, and process standardization are necessary for broader and more effective adoption.